2016
DOI: 10.1111/1754-9485.12473
|View full text |Cite
|
Sign up to set email alerts
|

Radiation dose and diagnostic image quality associated with iterative reconstruction in coronary CT angiography: A systematic review

Abstract: The aim of this systematic review is to evaluate the radiation dose reduction achieved using iterative reconstruction (IR) compared to filtered back projection (FBP) in coronary CT angiography (CCTA) and assess the impact on diagnostic image quality. A systematic search of seven electronic databases was performed to identify all studies using a developed keywords strategy. A total of 14 studies met the criteria and were included in a review analysis. The results showed that there was a significant reduction in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 39 publications
(227 reference statements)
2
12
0
Order By: Relevance
“…In a prior work, 20 the use of this new cardiac insert phantom had been demonstrated to determine the impact of various image reconstruction algorithms on image quality and dose reduction potential. The results were consistent with past studies [21][22][23] as the image datasets reconstructed with iterative reconstruction algorithm exhibited more noise reduction, hence resulting in higher image quality, when compared to the filtered back projection.…”
Section: Discussionsupporting
confidence: 92%
“…In a prior work, 20 the use of this new cardiac insert phantom had been demonstrated to determine the impact of various image reconstruction algorithms on image quality and dose reduction potential. The results were consistent with past studies [21][22][23] as the image datasets reconstructed with iterative reconstruction algorithm exhibited more noise reduction, hence resulting in higher image quality, when compared to the filtered back projection.…”
Section: Discussionsupporting
confidence: 92%
“…The results demonstrated that the IR ASIR 60% with a low tube voltage of 100 kVp produced comparable SNR to the current local CCTA protocols of 120 kVp and ASIR 40% resulting in a > 50% reduction in radiation dose as measured by the CTDI vol . In our previous systematic review, 22 we concluded that using an IR algorithm allows up to 41% dose reduction as compared to FBP while maintaining similar image quality. Our findings have revealed that although the IR algorithm is already a powerful tool to reduce dose, the higher IR strength at a lower tube voltage has resulted in a further dose reduction.…”
Section: Discussionmentioning
confidence: 87%
“…The 3D‐printed cardiac insert phantom, simulating the contrast‐enhanced region of the ascending aorta and coronary vessels in CCTA, was constructed using 3D printing technology and placed within an anthropomorphic chest phantom (Lungman N‐01, Kyoto Kagaku Co., Ltd., Kyoto, Japan). The development of the 3D‐printed cardiac insert phantom was described in our previous work 22 . The contrast medium used was Ultravist 370 (Schering Health Care Ltd, Burgess Hill, UK).…”
Section: Methodsmentioning
confidence: 99%
“…The volume of CT dose index (CTDI vol ) for the 4 protocols was 19.2 mGy, 11.6 mGy, 5.8 mGy and 2.9 mGy, representing dose reductions of 40%, 70% and 85%, respectively. These dose reductions were chosen based on the previous work 6 . The detector collimation was 1 x 16 mm, the display field of view (DFOV) was 350 mm, and gantry rotation time was 0.75 s. Data acquisitions of the phantom were repeated thirty times for each exposure settings.…”
Section: Acquisition Protocolsmentioning
confidence: 99%
“…However, FBP results in images that can be deteriorated by both electronic and quantum noise. 6 Iterative reconstruction (IR) algorithms allow using lowdose CT protocols while maintaining the image quality. It uses statistical noise models to optimise the image quality of the final image.…”
Section: Introductionmentioning
confidence: 99%